PENGARUH RASIO C/N AWAL DAN LAJU AERASI PADA PROSES CO-COMPOSTING BLOTONG DAN ABU KETEL - Andes Ismayana; Nastiti Siswi Indrasti; Niza Erica (Bumi Lestari Journal of Environment, 2014)
Co-composting was the composting process uses two or more raw materials to improve the optimization process and material benefits. The purpose of this study was to determine the influence of the initial C/N value ratio and the active aeration usage of the co-composting process of filter cake and boiler ash of cane sugar industry. Co-composting  was done in the aeration pile reactor with 5 kg of mixed material,and uused two factor; initial C/N ratio and aeration. The treatment of  C/N ratio was begun at 30, 40, and 50 from formulation filtercake and boiler ash.   Active aeration was given at 0.4 and 1.2 l /minutes.kg materials that carried out for 1 hour per day  on the first week. From this observation, known that the aeration distiction at 0.4 and 1.2 l /minutes.kg materials does not effect the C/N ratio of  compost.  In the other hand,  the treatment of initial C/N ratio at 30 and 40 was significantly affected with initial C/N ratio at 50 compared by final  C/N value of the compost. Initial C /N ratio at 50 requested the final  C / N ratio of compost at 19-20 that was higher than the treatment of  intial C/N ratio at 30 and 40 which had final C/N ratio at 13-15 and 12-17, respectively.